‘Only twice a year’: a qualitative exploration of 6-month antiretroviral treatment refills in adherence clubs for people living with HIV in Khayelitsha, South Africa - Keene, CM; Zokufa, N; Venables, EC; Wilkinson, L; Hoffman, R; Cassidy, T; Snyman, L; Grimsrud, A; Voget, J; von der Heyden, E; Zide-Ndzungu, S; Bhardwaj, V; et al. (BMJ Publishing Group, 2020)
Objective Longer intervals between routine clinic visits and medication refills are part of patient-centred, differentiated service delivery (DSD). They have been shown to improve patient outcomes as well as optimise health services—vital as ‘universal test-and-treat’ targets increase numbers of HIV patients on antiretroviral treatment (ART). This qualitative study explored patient, healthcare worker and key informant experiences and perceptions of extending ART refills to 6 months in adherence clubs in Khayelitsha, South Africa.